Method for achieving rapid boronizing of titanium metal surface through electric field induced nanometer assembly in fused salt

By using the nanoassembly method of electric field-induced nanoassembly in molten salt on the surface of titanium metal, using nanoTiB2 to form a boronated layer, the problems of high energy consumption and mechanical performance reduction caused by long-term boronation in high temperatures in the prior art are solved, and rapid, low energy consumption and high-performance boronation on the surface of titanium metal are achieved.

CN119530914AActive Publication Date: 2025-02-28ANHUI UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411722119.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing titanium surface boronation treatment technology needs to be carried out for a long time at high temperatures, resulting in high energy consumption and changes in the structure of the titanium matrix material, affecting the mechanical properties.

Method used

Using the nanoassembly method of electric field-induced nanoassembly in molten salt, nanoTiB2 is used as the assembly unit to accelerate TiB2 migration and deposition under the action of the electric field to form a rapid boronation layer on the surface of titanium metal.

Benefits of technology

It realizes rapid boronization of the titanium metal surface, simple operation, low energy consumption, short boronization time, and the formed boronized layer is dense, uniform in thickness, high hardness and strong bonding strength, which is suitable for use under various harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530914A_ABST
    Figure CN119530914A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal surface treatment, in particular to a method for achieving titanium metal surface rapid boronizing through electric field induction nanometer assembly in molten salt, titanium dioxide powder, boron powder, inorganic salt and a nanometer particle wrapping agent are evenly mixed, and the molten salt containing nanometer TiB2 is obtained after heating reaction. Graphite and a titanium metal part are put into molten salt containing nano TiB2, the graphite serves as a positive electrode, the titanium metal part serves as a negative electrode, the surface area ratio of the positive electrode to the negative electrode is (3-10): 1, the nano TiB2 in the molten salt is assembled on the surface of the titanium metal part under the action of an electric field to form a boronizing layer, and the boronizing speed is 60-500 microns / h. Compared with an existing high-temperature boronizing technology with active boron atoms as a constituent unit, the high-temperature boronizing technology has the advantages that the boronizing speed can be remarkably increased, the high-temperature boronizing treatment time of titanium metal is shortened, energy is saved, cost is reduced, and meanwhile the negative influence of the high-temperature environment on the organization structure and the mechanical property of a titanium metal part is eliminated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface treatment, and in particular to a method for realizing rapid boronization of titanium metal surface by adopting electric field-induced nano-assembly in molten salt. Background Art

[0002] Industrial pure titanium and titanium alloys have been widely used in cutting-edge technology fields such as aviation, aerospace, petrochemicals, automobile manufacturing, and biomedicine due to their low thermal expansion coefficient, excellent corrosion resistance, excellent specific strength and specific stiffness. Nevertheless, titanium metal itself has some inherent limitations, such as low hardness and insufficient wear resistance, which limit its potential in certain applications. In order to overcome these limitations, researchers have developed a series of surface modification technologies, including carburizing, oxidation, nitriding and boriding on the surface of titanium metal. These technologies are designed to improve the surface properties of titanium metal and make it more adaptable to diverse industrial needs.

[0003] Titanium boride has high hardness, excellent thermal conductivity and low resistivity. These characteristics make the formation of a boride layer on the surface of titanium metal an effective means to improve its performance and expand its application field. At present, the surface boriding treatment technology of titanium metal mainly includes solid powder boriding, salt bath boriding and molten salt electrolysis. However, these methods generally have a problem, that is, they need to be subjected to long-term boriding treatment at high temperatures of 800 to 1200°C, which usually takes 5 to 20 hours. This not only leads to higher energy consumption costs, but also changes the organizational structure of the titanium metal matrix material, thereby negatively affecting its mechanical properties. Therefore, how to improve the boriding speed of titanium metal has become a key issue that needs to be solved in the field of titanium metal surface boriding.

[0004] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that the existing boronization technology of titanium metal surface is that active boron atoms diffuse to the titanium metal surface under high temperature environment and react with titanium to form a boride layer. However, the diffusion rate of boron atoms is slow, which limits the realization of rapid boronization. A method for realizing rapid boronization of titanium metal surface by electric field induced nano-assembly in molten salt is provided. The technical principle of the present invention is to use nano-TiB2 as the assembly unit and utilize electric field induction to accelerate the migration and deposition of TiB2.

[0006] In order to achieve the above object, the present invention discloses a method for realizing rapid boronization of titanium metal surface by using electric field induced nanoassembly in molten salt, comprising the following steps:

[0007] S1, mixing titanium dioxide powder, boron powder, inorganic salt, and nanoparticle encapsulating agent, and heating to react to obtain molten salt containing nano-TiB2;

[0008] S2, putting graphite and titanium metal parts into molten salt containing nano-TiB2, with graphite as the positive electrode and titanium metal parts as the negative electrode. Nano-TiB2 in the molten salt assembles on the surface of the titanium metal parts under the action of the electric field to form a boronized layer.

[0009] In step S1, the inorganic salt is a combination of any two or three of NaCl, KCl, MgCl2, NaF, LiF, KF and AlF3.

[0010] In the step S1, the concentration of nano-TiB2 in the molten salt containing nano-TiB2 is 100-200 g / L, and the particle size of TiB2 is 2-20 nm.

[0011] In the step S1, the nanoparticle encapsulating agent is any one or two of boron trioxide, silicon dioxide, tin dioxide and aluminum trioxide, and the concentration of the nanoparticle encapsulating agent in the molten salt is 3-8wt%.

[0012] In step S2, the material of the titanium metal part is any one of industrial pure titanium, Ti-6Al-4V, Ti-5Al-2.5Sn and Ti-6Al-6V-2Sn.

[0013] In the step S2, the surface area ratio of the positive electrode to the negative electrode is 3 to 10:1.

[0014] In the step S2, the electric field strength is 0.3-1.2 V / cm.

[0015] In the step S2, the boride layer includes a transition layer TiB and a working layer TiB2.

[0016] In the step S2, the boride layer forming speed is 60-500 μm / h.

[0017] Compared with the prior art, the beneficial effects of the present invention are:

[0018] 1. The present invention provides a boronization method based on a new principle, which has a simple operation method, short boronization time, low energy consumption, and little effect on the microstructure and mechanical properties of titanium metal matrix materials;

[0019] 2. The boride layer formed by the present invention has the characteristics of being fully dense and uniform in thickness, and the transition layer TiB does not contain needle-like structures, which not only reduces the brittleness of the boride layer, but also makes its hardness reach more than 4000HV;

[0020] 3. The boride layer formed by the present invention has a TiB transition layer of a certain thickness, which ensures that the bonding strength between the boride layer and the substrate is above 100N (using the scratch method as the test standard), and can meet the use under various harsh conditions;

[0021] 4. The molten salt medium used in the present invention has a purifying effect on the surface of titanium metal parts. Only simple treatment is required before boriding, and no complex surface pretreatment such as grinding is required. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a TEM image of the solid salt obtained after cooling the molten salt containing nano-TiB2;

[0023] Figure 2 This is a low-magnification SEM image of the cross section of the borided layer obtained by rapid boriding of industrial pure titanium;

[0024] Figure 3 This is a high-magnification SEM image of a local cross-section of the borided layer obtained by rapid boriding of industrial pure titanium;

[0025] Figure 4 This is the result of the scratch test on the bonding strength of industrial pure titanium with surface boronization.

[0026] Figure 5 This is the hardness test result of the boronized layer on the surface of industrial pure titanium;

[0027] Figure 6 This is the test result of the friction coefficient of the boronized layer on the surface of industrial pure titanium;

[0028] Figure 7 The cross-sectional SEM image of the borided layer obtained by rapid boriding of TC4 titanium alloy and the corresponding mapping analysis;

[0029] Figure 8 This is the TEM image of the transition layer of the borided layer obtained by rapid boriding of TC4 titanium alloy;

[0030] Fig. 9 This is a SEM image of the solid salt obtained after cooling the molten salt containing nano-TiB2 in Comparative Example 1;

[0031] Fig.10 This is a cross-sectional SEM image of the boronized layer obtained in Comparative Example 1;

[0032] Fig.11 This is a cross-sectional SEM image of the boronized layer obtained in Comparative Example 2;

[0033] Fig.12 This is the SEM image of TiB2 sheets agglomerated in solid salt in Comparative Example 2. DETAILED DESCRIPTION

[0034] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0035] Example 1

[0036] Rapid boronization was performed on the surface of industrial pure titanium. First, a molten salt containing nano-TiB2 was synthesized, and B powder (average particle size 1μm) and TiO2 powder (average particle size 100nm) were mixed in a molar ratio of 4:1 to obtain a mixed raw material of the reactant. The inorganic salt was NaF and AlF3 salts in a molar ratio of 1:1.2. The nanoparticle encapsulating agent was Al2O3 (average particle size 5μm). The mixed raw material of the reactant, the inorganic salt and the nanoparticle encapsulating agent were mixed evenly in a mass ratio of 1:10:0.5 and placed in a graphite crucible. The graphite crucible was heated to 900℃ and kept warm for 2 hours to obtain TiB2 particles with a particle size of 3nm. Then, electric field induced nanoassembly was performed in a molten salt containing nano-TiB2. A graphite positive electrode and an industrial pure titanium negative electrode were inserted into the molten salt, the surface area ratio of the positive electrode to the negative electrode was 5:1, a voltage of 1.2V was applied, the corresponding electric field strength was 0.6V / cm, and the assembly time was 50min. The industrial pure titanium after the boriding treatment is taken out and placed in molten NaCl-KCl at 690°C for cleaning for 5 minutes to remove the residual solid salt on the surface of the boriding layer, and then washed with water and dried to obtain a fully dense boriding layer with a thickness of 70 μm.

[0037] Figure 1 The TEM test results of the solid salt obtained after cooling the molten salt containing nano-TiB2 are shown in Figure 1. Figure 1 It can be seen that TiB2 particles with a particle size of about 3 nanometers were synthesized by reaction in the molten salt; Figure 2 and Figure 3 They are the low-magnification and local high-magnification SEM analysis results of the cross-section of the borided layer obtained by rapid boriding of industrial pure titanium. The results show that the average thickness of the borided layer is 70μm, the boriding speed is 84μm / h, and the borided layer is composed of TiB and TiB2. Figure 4 The scratch test results of bonding strength of industrial pure titanium with surface boronization show that the bonding strength is greater than 100N. Figure 5 and Figure 6 The hardness and friction coefficient test results of the borided layer on the surface of industrial pure titanium are shown respectively. The average hardness is 4007HV and the average friction coefficient is 0.13. The bonding strength, hardness and friction coefficient of the obtained borided layer fully meet the application requirements.

[0038] Example 2

[0039] Rapid boronization treatment was performed on the surface of TC4 titanium alloy (Ti-6Al-4V). First, a molten salt containing nano-TiB2 was synthesized, and B powder (average particle size 1μm) and TiO2 powder (average particle size 100nm) were mixed at a molar ratio of 4.2:1 to obtain a mixed raw material of the reactant. The inorganic salts were NaCl, KCl and AlF3 salts in a molar ratio of 1:1:0.5. The nanoparticle encapsulating agent was SiO2 (average particle size 0.8μm). The mixed raw material of the reactant, the inorganic salt and the nanoparticle encapsulating agent were mixed evenly at a mass ratio of 1:11:0.4 and placed in a graphite crucible. The graphite crucible was heated to 930℃ and kept warm for 3 hours to obtain TiB2 particles with a particle size of 10nm. Then, electric field induced nanoassembly was performed in the molten salt containing nano-TiB2. The graphite positive electrode and the TC4 titanium alloy negative electrode were inserted into the molten salt, the surface area ratio of the positive electrode to the negative electrode was 6:1, a voltage of 1.3V was applied, the corresponding electric field strength was 0.5V / cm, and the assembly time was 60min. The TC4 titanium alloy after the boronization treatment was taken out and placed in 700℃ molten NaCl-KCl for 6min to remove the residual solid salt on the surface of the boronized layer, and then washed and dried to obtain a fully dense boronized layer with a thickness of 110μm.

[0040] Figure 7 The following is a cross-sectional SEM image of the boriding layer obtained after rapid boriding treatment on the surface of TC4 titanium alloy (Ti-6Al-4V) and the corresponding mapping analysis. The results show that the average thickness of the boriding layer is 110μm and the boriding rate is 110μm / h. The interface between the substrate and the coating was analyzed by TEM. The results are as follows Figure 8 As shown. Figure 8 It can be seen that there is a 1 μm thick TiB layer at the coating interface, which forms a transition layer between the borided layer and the TC4 titanium alloy substrate, forming a metallurgical bond and ensuring that the borided layer and the substrate have a bonding strength that meets the use requirements.

[0041] Example 3

[0042] Rapid boronization treatment was performed on the surface of TA7 titanium alloy (Ti-5Al-2.5Sn). First, a molten salt containing nano-TiB2 was synthesized, and B powder (average particle size 1μm) and TiO2 powder (average particle size 100nm) were mixed at a molar ratio of 4.5:1 to obtain a mixed raw material of the reactant. The inorganic salts were KF, NaF and AlF3 salts with a molar ratio of 1:1:1.2. The nanoparticle encapsulating agent was SnO2 (average particle size 2μm). The mixed raw material of the reactant, the inorganic salt and the nanoparticle encapsulating agent were mixed evenly at a mass ratio of 1:12:0.2 and placed in a graphite crucible. The graphite crucible was heated to 890℃ and kept warm for 5 hours to obtain TiB2 particles with a particle size of 12nm. Then, electric field induced nanoassembly was performed in the molten salt containing nano-TiB2. The graphite positive electrode and the TA7 titanium alloy negative electrode were inserted into the molten salt, the surface area ratio of the positive electrode to the negative electrode was 9:1, a voltage of 1.4V was applied, the corresponding electric field strength was 0.9V / cm, and the assembly time was 40min. The TA7 titanium alloy after the boronization treatment was taken out and placed in molten NaCl-KCl at 700℃ for 7min to remove the residual solid salt on the surface of the boronized layer, and then washed and dried to obtain a fully dense boronized layer with a thickness of 150μm.

[0043] Comparative Example 1

[0044] The boronized coating on the surface of industrial pure titanium was prepared by electric field induced nanoassembly in molten salt. The specific implementation steps were the same as those in Example 1, except that the nanoparticle encapsulating agent Al2O3 was not added. The SEM of the obtained nano-TiB2 solid salt was as follows: Fig. 9 As shown by Fig. 9 It can be seen that without adding nanoparticle encapsulating agent, TiB2 particles with a size range of 50-100nm are formed in the molten salt. After the molten salt containing large particles of TiB2 is subjected to electric field induced assembly, the SEM analysis of the cross section of the formed coating is as follows: Fig.10 As shown. Fig.10 It can be seen that the coating is not a single dense boronized coating, but is composed of two dense boronized layers with a layer of solid salt in the middle. This shows that TiB2 particles with a particle size of 50 to 100 nm in the molten salt are not conducive to the realization of rapid boronization.

[0045] Comparative Example 2

[0046] The boronized coating on the surface of industrial pure titanium was prepared by electric field induced nanoassembly in molten salt. The specific implementation steps were the same as those in Example 1, except that the nanoparticle encapsulating agent Al2O3 was not added, and the ratio of the surface area of ​​the positive electrode to the negative electrode was adjusted to 9. The cross-section SEM analysis of the final coating was as follows: Fig.11 As shown, from Fig.11 It can be seen that only a layer of solid salt rich in TiB2 particles adheres to the electrode surface, and no boronized layer is formed. At the same time, SEM analysis of the solid salt after the boronization treatment is performed, such as Fig.12 As shown, from Fig.12 It can be seen that there are a large number of agglomerated TiB2 sheets in the solid salt, which indicates that when the surface area ratio of the positive electrode to the negative electrode is adjusted to 9, nano-TiB2 easily loses stability during migration and aggregates in the molten salt to form TiB2 sheets, but cannot reach the surface of the titanium matrix to form a boride layer.

[0047] The nanoparticle sizes and cross-sectional morphologies of the coatings obtained in Example 1 and Comparative Examples 1-2 were observed, and the results are shown in Table 1.

[0048] Table 1 Comparison of key process parameters and implementation effects of the embodiment and comparative examples 1-2

[0049]

[0050] As can be seen from Table 1, the nanoparticle encapsulation agent plays a key role, that is, it can assist in the synthesis of TiB2 with a size of less than 20nm in the molten salt. Nano-TiB2 of this size can achieve the preparation of a flat and fully dense boronized layer at a high positive electrode to negative electrode area ratio, thereby achieving a high boronization rate. Without the addition of the nanoparticle encapsulation agent, the size of the nanoparticles can only be in the range of 50 to 100nm. When a higher positive electrode to negative electrode area ratio is used, large-sized nano-TiB2 is easy to agglomerate and sink during the electric field induced migration process, and a normal boronized layer cannot be obtained.

[0051] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. A method for realizing rapid boronization of titanium metal surface by electric field induced nanoassembly in molten salt, characterized in that: The following steps are involved: S1, mixing titanium dioxide powder, boron powder, inorganic salt, and nanoparticle encapsulating agent, and heating to react to obtain molten salt containing nano-TiB2; S2, putting graphite and titanium metal parts into molten salt containing nano-TiB2, with graphite as the positive electrode and titanium metal parts as the negative electrode. Nano-TiB2 in the molten salt assembles on the surface of the titanium metal parts under the action of the electric field to form a boronized layer.

2. A method for realizing rapid boronization of titanium metal surface by electric field induced nanoassembly in molten salt according to claim 1, characterized in that: In step S1, the inorganic salt is a combination of any two or three of NaCl, KCl, MgCl2, NaF, LiF, KF and AlF3.

3. The method of realizing rapid boronization of titanium metal surface by electric field induced nanoassembly in molten salt according to claim 1, characterized in that: In the step S1, the concentration of nano-TiB2 in the molten salt containing nano-TiB2 is 100-200 g / L, and the particle size of TiB2 is 2-20 nm.

4. The method of realizing rapid boronization of titanium metal surface by electric field induced nanoassembly in molten salt according to claim 1, characterized in that: In the step S1, the nanoparticle encapsulating agent is any one or two of boron trioxide, silicon dioxide, tin dioxide and aluminum trioxide, and the concentration of the nanoparticle encapsulating agent in the molten salt is 3-8wt%.

5. The method of realizing rapid boronization of titanium metal surface by electric field induced nanoassembly in molten salt according to claim 1, characterized in that: In the step S2, the material of the titanium metal part is any one of industrial pure titanium, Ti-6Al-4V, Ti-5Al-2.5Sn and Ti-6Al-6V-2Sn.

6. The method of realizing rapid boronization of titanium metal surface by electric field induced nanoassembly in molten salt according to claim 1, characterized in that: In the step S2, the surface area ratio of the positive electrode to the negative electrode is 3 to 10:

1.

7. The method of realizing rapid boronization of titanium metal surface by electric field induced nanoassembly in molten salt according to claim 1, characterized in that: In the step S2, the electric field strength is 0.3-1.2 V / cm.

8. The method of realizing rapid boronization of titanium metal surface by electric field induced nanoassembly in molten salt according to claim 1, characterized in that: In the step S2, the boride layer includes a transition layer TiB and a working layer TiB2.

9. The method of realizing rapid boronization of titanium metal surface by electric field induced nanoassembly in molten salt according to claim 1, characterized in that: In the step S2, the boride layer is formed at a speed of 60 to 500 μm / h.

Citation Information

Patent Citations

  • Method for preparing TiB2 powder

    CN108584972A

  • Method for preparing transition metal boride coating through fused salt in-situ synthesis and electrophoretic deposition

    CN114045546A

  • Method for preparing TiB2 cathode coating on line through electrophoretic deposition in aluminum electrolyte

    CN114990634A

Cited By

  • Method for electrophoretic deposition of metal boride coating on surface of special-shaped cathode in molten salt

    CN120797141A

  • Preparation method of TiB2 coating for inhibiting particle aggregation in electrophoretic deposition process

    CN122080683A